Studies in Mineral Nutrition of Indian forest Tree Species. 1. Effect of Deficiency of Macro-nutrients on Growth of Salmalia Malabarica Schott. and Endl. under Varying Light Conditions - Nanda, K. K. (Indian Forester, 1963)
Fifty-five day old seedlings of Salmalia malabarica were transferred under three light conditions - (1) Long Day (LD); (2) Normal Day (ND); and (3) Light of low intensity - and were divided into eight lots each. One lot received solution deficient in all major elements. The second lot received complete nutrient solution and served as control. Of the remaining six lots each received nutrient solutions deficient in one of the macroelements - N, P, K, Ca, Mg or S. Periodical records were taken of height; number, size and abscission of leaves and the visual symptoms. The rate of stem elongation was higher and extension growth continued for a longer period under LD than under ND condition. Plants under LD, therefore, were taller than those under NO at all stages of growth. The number and size of leaves was also higher under LD than under ND, while during the earlier stages of growth this higher number was due to the higher rate of production of new leaves, during the later stages it was due mainly to the slower rate of their abscission. Macro-nutrient deficiencies retarded stem growth, production of leaves and their size. The retarding effect was most marked in plants deficient for all major elements and decreased in order in those deficient for N. P, K and S. The deficiencies of Ca or Mg did not affect the growth of these parts to any appreciable extent. The abscission of leaves was more in plants deficient for Mg, P and K than in those deficient for N. In plants deficient for S the abscission of leaves was low and compared favourably with the controls. The deficiencies of different macro-elements caused very distinctive visual symptoms and a key is presented on the basis of these results to help in the diagnosis of deficiency diseases in the field. The differentiating symptoms did not show up under low intensity of light. Plants under this light-condition were weak and died after a few weeks. The deficiency symptoms showed up more distinctly under LD than under ND. This was probably because of the prolonged growing period under this light treatment due to delayed onset of dormancy. The significance of interaction of factors in the study of problems in mineral nutrition of tree species is stressed and the results are discussed in the light of investigations by other workers.